Effect of sequential mechanical ventilation therapy on alveolar oxygenation function and systemic inflammatory response syndrome in patients with severe pneumonia and respiratory failure - Rong Hu (Journal of Hainan Medical University, 2016)
Objective: To study the effect of sequential mechanical ventilation therapy on alveolar oxygenation function and systemic inflammatory response syndrome in patients with severe pneumonia and respiratory failure. Methods: A total of 92 patients who were diagnosed with severe pneumonia and required mechanical ventilation therapy in our hospital from May 2012 to October 2015 were selected and randomly divided into two groups, sequential group received invasive-non-invasive sequential mechanical ventilation therapy and routine group received conventional invasive mechanical ventilation therapy. Three days after treatment, blood gas analysis parameters, mechanical ventilation parameters, the levels of inflammatory cytokines, cardiac function injury molecules, kidney damage molecules in serum and the levels of kidney damage molecules in the urine were compared between two groups of patients. Results: Three day after treatment, PaO2, HCO3 - , TI, TE and TPTEF of sequential group were significantly higher than those of routine group; serum IL-6, TNF-α, sTREM-1, IL-4, IL- 10, IL-13, ANP, BNP, NPY, cTnI, CYS, NGAL and KIM-1 levels of sequential group were significantly lower than those of routine group, and urine NGAL, KIM-1 and Netrin-1 levels were significantly lower than those of routine group. Conclusions: Invasive-non-invasive sequential mechanical ventilation therapy can improve the alveolar oxygenation function and reduce the systemic inflammatory response as well as cardiac function and renal function injury in patients with severe pneumonia and respiratory failure.